DNA microsatellite analysis of families with autosomal dominant polycystic kidney disease types 1 and 2: evaluation of clinical heterogeneity between both forms of the disease. Issue 6 (June 1995) - Coto, E; Sanz de Castro, S; Aguado, S; Alvarez, J; Arias, M; Menéndez, M J; López-Larrea, C
Abstract : We studied 17 large families affected by adult dominant polycystic kidney disease (ADPKD). Ultrasonographic analysis was performed on all the family members. DNA microsatellite markers closely linked to PKD1 on 16p13.3 were analysed, and linkage of the disease to this locus was determined. Families showing a negative linkage value were evaluated for linkage to the PKD2 locus on 4q. Five of the 17 families showed negative linkage for the 16p13.3 markers. In these families significant linkage to 4q was obtained. Renal cysts developed at an earlier age in PKD1 mutation carriers, and end stage renal failure occurred at an older age in people affected with PKD2. Analysis of large families with ADPKD in a Spanish population indicates that this is a genetically heterogeneous disorder, but mutations at only two loci are responsible for the development of the disease in most if not all the families. Clinicopathological differences between both forms of the disease occur, with subjects with ADPKD2 having a better prognosis than those with mutations at PKD1.